Evaluación de diferentes niveles de Coenzima Q10 en los parámetros zootécnicos y fisiológicos en el síndrome de hipertensión pulmonar en aves de engorde. - Concha Romero, Luis Gerardo (2024)
The present research was carried out in the parish of San Gerardo, belonging to the province of Chimborazo where oximetry, heart rate, hematocrit, ventricular relationship, mortality, and the cost-benefit analysis of coenzyme Q10 were evaluated in birds raised at 2670 amsl. Coenzyme Q10 was administered in three treatments: T1 10 mg/kg; T2 20 kg/mg and T3 30 mg/kg, to be compared with a control treatment 0 mg/kg, A commercial feed was provided with coenzyme Q10, the data were obtained on 7, 14, 21, 28 and were analyzed with the help of the Infostat software to be subjected to an analysis with ADEVA and a separation of means according to Duncan. The addition of coenzyme Q10 increased oximetry levels during days 7, 14, 21 and 28 in the T2 and T3 treatments due to its influence on electron transport within the mitochondrial chain, contributing to the strengthening of cellular respiration and improving the contractility of the heart. T2 and T3 treatments reduced the percentage of mortality compared to the control group by preventing lipid peroxidation while maintaining the required levels of ubiquinone. The highest B/C $1.02 is reported by the control treatment; while a lower profitability is presented by treatment 1 and 3 B/C $0.92. In conclusion, the inclusion of Coenzyme Q10 in broiler feed is an effective strategy to reduce mortality from pulmonary hypertension. Coenzyme Q10 supplementation improved the cardiovascular health of the birds, significantly decreasing mortality and improving oxygenation levels compared to the control group.